Evaluasi Mikrobiologis dan Organoleptik Daging Se’i Sapi yang Diberi Perlakuan Beberapa Jenis Asap Cair - Novallino H. G. Kallau (JURNAL KAJIAN VETERINER, 2019)
A study about evaluating the microbiological quality and organoleptic beef cows se'i treated some kind of liquid smoke has been done using se'i bovine meat derived from beef obtained at RPH Oeba. The treatment given is injecting and soaking meat in beef se'i liquid smoke coming from the type of wood of bidara and wood of kusambi and curing of meat se'i cow as a control; then se'i cow meat is stored and sampled every 0 days, 5 days and 10 days. The observations made include microbiological quality (total number of colonies / TPC and Coliform), organoleptic quality (odour, color, flavor and tenderness), and pH se'i beef cattle. The results showed the number of TPC is affected by the method and type of smoke injection method is better in maintaining the TPC; pH se'i beef cattle are influenced by the type of smoke; type of liquid smoke kusambi better in maintaining the pH of the meat; odour influenced by the type of meat se'i smoke and the old store; the smell of wood smoke generated by kusambi is better; se'i meat flavor is influenced by the type of smoke and the old store; results kusambi wood smoke flavor the meat has a better se'i; se'i beef meat color is affected by the method; immersion method showed a better effect in maintaining se'i beef meat color.